2018
DOI: 10.1007/s11255-017-1784-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of zinc in urinary stone disease

Abstract: In recent years, the role of trace elements in lithogenesis has received steadily increasing attention. It is well documented that some trace elements can influence the morphology and speed of the crystallization process. Zinc has been found in significant amounts in calcium stones relative or organic stones (uric acid and cystine), probably substituting calcium in crystals because of their similarity in charge and size. High Zn levels are present in carbapatite of Randal's plaques suggesting that zinc could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Thus, it is likely, that some of these elements may also play an important, however not yet understood, role in early pathological calcification processes. For example, recent studies (Chi et al, 2015;Ramaswamy et al, 2015;Negri, 2018) report that renal papillae and Randall's Plaque are enriched in Zn, suggesting that this essential trace metal might play a role or be linked to early calcification processes. Gaining insight into the role of Zn (and other essential trace metals) in the underlying pathophysiology of early stone formation necessitates the simultaneous study of major and trace elements at multi-length scales in tissular, cellular, and subcellular context.…”
Section: Pathological Calcificationmentioning
confidence: 99%
“…Thus, it is likely, that some of these elements may also play an important, however not yet understood, role in early pathological calcification processes. For example, recent studies (Chi et al, 2015;Ramaswamy et al, 2015;Negri, 2018) report that renal papillae and Randall's Plaque are enriched in Zn, suggesting that this essential trace metal might play a role or be linked to early calcification processes. Gaining insight into the role of Zn (and other essential trace metals) in the underlying pathophysiology of early stone formation necessitates the simultaneous study of major and trace elements at multi-length scales in tissular, cellular, and subcellular context.…”
Section: Pathological Calcificationmentioning
confidence: 99%
“…We also observe a decrease in the number of crystals (Figure S3) with increasing Zn 2+ concentration, which is indicative of inhibited nucleation. These observations reveal Zn 2+ to be a moderately effective inhibitor of COM crystallization, consistent with a subset of published in vitro assays and epidemiological studies. …”
Section: Resultsmentioning
confidence: 99%
“…Trace elements especially zinc, have been associated with kidney stone formation, although this is still controversial, as different studies have reported that dietary zinc intake is not even related to kidney stones. Discrepancy might be attributed to that zinc at low levels could inhibit the crystal growth, while higher doses might boost the production of amorphous calcium phosphate [111,112].…”
Section: Adulthood and The Elderlymentioning
confidence: 99%